Better Students Ask More Questions.
Combine the equations W = mg and `s = 1/(2*g*t^2)` to give an equation for W which...
2 Answers | add yours
From the equations W = mg and `s = 1/(2*g*t^2)` an expression for W has to be created that does not contain g.
`s = 1/(2*g*t^2)`
=> `2g*t^2 = 1/s`
=> `g = 1/(s*2*t^2)`
Substitute this for g in W = mg
=> `W = m/(s*2*t^2)`
The required expression is `W = m/(2*s*t^2)`
Posted by justaguide on June 20, 2012 at 7:03 AM (Answer #1)
The answer to this should have actually been 2ms/t^2
Posted by minnsy229 on June 22, 2012 at 2:51 PM (Answer #2)
Join to answer this question
Join a community of thousands of dedicated teachers and students.